Transepidermal Water Loss Value Comparison Between Tengkawang and Durian Seed Oil Lotion - Febriaty, Irma Ramadhani; Usman, Thamrin; Alimuddin, Andi Hairil (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Body epidermis has an important health function to prevent body dehydration. This research aims to compare Transepidermal Water Loss (TEWL) values between durian seed oil and tengkawang oil. Skin that had been applied with tengkawang oil and durian seed oil lotion were tested for irritation and TEWL values. The tengkawang oil had an acid number of 17 g/mol and contained 8.54 % free fatty acid, while the durian seed oil had an acid number of 6.34 g/mol and contained 2.89 % free fatty acid. Irritation testing was done using lotion containing 100 % of each oil. TEWL analysis on skin applied with the tengkawang oil lotion after 1 hour showed that the lotion could reduce epidermal water evaporation by 35.23 % compared to the skin condition before treatment. Epidermal water evaporation reduction at the second, third and fourth hours after the tengkawang oil lotion application was 31.33 %, 33.93 % and 27.9 %, respectively. TEWL analysis on skin applied with the durian seed oil lotion after 1 hour showed that the lotion could reduce epidermal water evaporation by 11.34 % compared to the skin condition before treatment. Epidermal water evaporation was reduced 14.64 %, 10.53 % and 2.99 % at the second, third and fourth hours after application of the durian seed oil. Based on these results, it can be concluded that tengkawang oil gives better TEWL values compared to durian seed oil.